Effect of bubble volume fraction on the shear and extensional rheology of bubbly liquids based on guar gum (a Giesekus fluid) as continuous phase. (February 2015) - Torres, M.D.; Hallmark, B.; Wilson, D.I.
Highlights: Bubbly liquids with bubble volume fraction ϕ < 25% studied in steady shear and extension. The guar gum continuous phase exhibited Giesekus fluid behaviour. The bubbly liquids also exhibited Giesekus fluid behaviour with parameters = f ( ϕ ). Noticeable differences between solutions in semi-dilute and entangled regimes. Smaller bubble sizes generated by syringing had little effect in semi-dilute regime. Abstract: The effect of air bubble volume fraction, ϕ, on the steady shear and extensional rheology of aqueous guar gum solutions was studied at 0 ⩽ ϕ ⩽ 0.25 and gum concentrations of (i) 5 g/L and (ii) 10 g/L, corresponding to solutions in the (i) semi-dilute and (ii) entanglement regime. The rheological response of the fluids was largely independent of bubble size but strongly dependent on ϕ . The viscous and elastic moduli increased with increasing bubble volume fraction, with elastic dominance prevalent at the higher gum concentration. Extensional rheometry, investigated using filament stretching, revealed that the thinning dynamics of the liquid thread were affected by bubble size, but the filament rupture time was primarily dependent on ϕ . The rheological behaviour in both shear and extension could be modelled as a single mode Giesekus fluid, with a single set of parameters able to describe both the shear and extensional behaviour in the semi-dilute regime. In the entanglement regime the single mode Giesekus fluid could fit the shear data or the extensional data individually, but not both. The fitted Giesekus fluid model parameters exhibited a strong dependency on ϕ, offering a way to predict the flow behaviour of these complex food fluids.